Education, Identity, and Recognition: The Shi‘i Islamic Education in Indonesia - Zulkifli, Zulkifli (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
This article seeks to explain the role of education in relation to identity formation and the problems of recognition among Indonesian Shi’i (Shi’a) educational institutions. Despite being relatively small in numbers, the existence of the Shi’i community in Indonesia has attracted great attention from the state and religious authorities, especially since the recent sectarian violence committed against minority groups. This article follows three basic arguments: first, the issue of recognition is essential for education; second, social recognition is central to identity formation; and third, educational institution is a site of identity formation. This study shows that education is a very important vehicle for the Shi’i group to gain recognition from the Sunni majority. Education plays an important role, and the Shi’i school system adopted from Iran has provided recognitive process and recognitive space for the community to make Shi’ism a legitimate group in Indonesian Islam.DOI: 10.15408/sdi.v21i1.879